2018
DOI: 10.1007/s12328-018-0832-x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic chylous ascites in a patient with HIV infection: response to total parenteral nutrition and octreotide therapy

Abstract: The authors describe a 47-year-old man infected with human immunodeficiency virus admitted for ascites and weight loss. Ascitic fluid analysis revealed chylous ascites (triglycerides 444 mg/dl) with negative microbiological tests. Neoplasia, cardiac disease and liver cirrhosis were excluded after an extensive diagnostic workout. Exploratory laparotomy with tissue sampling did not clarify ascites etiology. During hospital admission, patient status gradually deteriorated, severe malnutrition developed and ascite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…A definitive treatment in view of future cancer risk and debilitating morbidity is surgical, subtotal, or total gastrectomy [ 2 , 15 ]. Octreotide at a dose of 100 to 600 micrograms daily has been shown to be beneficial in case reports as it acts by modulating the TGF-alpha-EGFR pathway, which is the underlying pathogenic mechanism [ 16 ]. In recent cases, cetuximab and monoclonal antibodies to EGFR have been successfully used to treat MD [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A definitive treatment in view of future cancer risk and debilitating morbidity is surgical, subtotal, or total gastrectomy [ 2 , 15 ]. Octreotide at a dose of 100 to 600 micrograms daily has been shown to be beneficial in case reports as it acts by modulating the TGF-alpha-EGFR pathway, which is the underlying pathogenic mechanism [ 16 ]. In recent cases, cetuximab and monoclonal antibodies to EGFR have been successfully used to treat MD [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide has the potential to affect the TGF-α-EGFR pathway, which can be held liable for the proliferation of gastric mucosa [2,16].…”
Section: Treatmentmentioning
confidence: 99%
“…The medication attaches to the EGF receptor, which diminishes the formation of TGF-α. Its consumption has prevented gastrectomy and improved patient's quality of life [2,16]. Surgical treatment is an option for selected cases of Menetrier's disease, specifically for patients experiencing intractable pain, symptomatic and remarkable hypoalbuminemia, chronic hemorrhage, obstruction of the gastrointestinal tract, and when gastric cancer cannot be ruled out.…”
Section: Treatmentmentioning
confidence: 99%
“…Most previous studies are case reports that report the use of antibiotics, 128 glucocorticoids, 129 and acid‐suppressants, 130 etc. A previous study has indicated that long‐acting somatostatin may be effective for the treatment of Ménétrier's disease, 131 and that hypoalbuminemia and anemia should be corrected concurrently. The treatment of eosinophilic gastritis requires an investigation into the potential allergic factors and elimination of allergens, although some patients also require steroid therapy 132 .…”
Section: Clinical Issues and Statementsmentioning
confidence: 99%